Metabolomics study of 3-O-p-(Z/E)-coumaroyltormentic acid-treated Trypanosoma brucei brucei - Lúcia Mamede; Fanta Fall; Madeline Vast; Kristelle Hughes; Giorgia Martelli; Francesco Caligiore; Bernadette Govaerts; Paul A.M. Michels; Michel Frédérich; Joëlle Quetin-Leclercq (International Journal for Parasitology: Drugs and Drug Resistance)
Trypanosomiasis is a parasitic disease for which new treatments are needed due to the frequent occurrence of adverse side effects of current available drugs. Natural compounds found in traditionally used plants offer opportunities to discover innovative compounds that could prove pivotal to antitrypanosomal drug development. 3-O-p-(Z/E)-coumaroyltormentic acids (CTA) were isolated first from the West Africa-native tree Vitellaria paradoxa and have demonstrated quite selective in vitro and in vivo antitrypanosomal activity, despite the unknown mode of action. In this study, a metabolomics analysis using the data from both LC-HR-MS and 1H-NMR described CTA's effects on Trypanosoma brucei after 3 h exposure under 5 or 10 x EC50. Our study shows CTA's activity impacted tryptophan metabolism and reveals potential targets in different branches of this metabolism. Our results demonstrate a likely presence of enzymes dedicated to tryptophan, like a tryptophan aminotransferase, tryptophan 2,3-dioxygenase and/or indoleamine 2,3-dioxygenase, and other enzymes of the kynurenine pathway, despite the absence of their description thus far in this species. These data further implicate that CTA's toxic effect on the tryptophan metabolism may be attributed to the decrease of the intracellular level of essential aspartate, resulting from inhibition of its aminotransferase. In resume, our study shines light on the likelihood of the tryptophan metabolism pathway presenting innovative targets toward the development of antitrypanosomal drugs. These require confirmation through functional and enzymatic studies.